2011
DOI: 10.1200/jco.2011.29.15_suppl.e16001
|View full text |Cite
|
Sign up to set email alerts
|

Weekly cisplatin versus standard three-weekly cisplatin in concurrent chemoradiotherapy of head and neck cancer: Baskent University experience.

Abstract: Cooper et al., 2004). This regimen is, however, usually associated with significant increase in acute toxicities such as higher rate of mucositis, hematological complication, and renal complication. Occurrence of these side effects can be resulted with early treatment termination or at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 11 publications
5
24
2
3
Order By: Relevance
“…The main reasons for this observation of some difference in toxicity could have been forced hydration and post-CT care of patients which was mandatory only for 3-weekly arm as suggested by the authors (Tsan et al, 2012). Similar findings were seen in a retrospective analysis of 55 patients by Kose et al demonstrating a higher incidence of grade III -IV mucositis with the weekly regimen (Kose et al, 2011). They reported that patients with grade III -IV mucositis during CRT had significantly higher median OS than those DOI:http://dx.doi.org/10.7314/APJCP.2016.17.4…”
Section: Acute Toxicity (Mucositis Dermatitis)supporting
confidence: 74%
See 1 more Smart Citation
“…The main reasons for this observation of some difference in toxicity could have been forced hydration and post-CT care of patients which was mandatory only for 3-weekly arm as suggested by the authors (Tsan et al, 2012). Similar findings were seen in a retrospective analysis of 55 patients by Kose et al demonstrating a higher incidence of grade III -IV mucositis with the weekly regimen (Kose et al, 2011). They reported that patients with grade III -IV mucositis during CRT had significantly higher median OS than those DOI:http://dx.doi.org/10.7314/APJCP.2016.17.4…”
Section: Acute Toxicity (Mucositis Dermatitis)supporting
confidence: 74%
“…Contradictory to this, various studies have reported no difference in terms of hematological toxicities between the two comparative arms (Kose et al, 2011;Tsan et al, 2012).…”
Section: 1617 Three Weekly Versus Weekly Cisplatin As Radiosensitizementioning
confidence: 99%
“…As published in 2012, Tsan et al randomized 55 postoperative high-risk SCCHN cases of the oral cavity between weekly and three-weekly regimens, demonstrating superiority of the latter scheme both in terms of compliance and toxicity [33]. Additionally, six studies retrospectively investigating the same comparison yielded outcomes favoring neither of these two schedules (Table 3) [26,[78][79][80][81][82].…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that up to 87% of patients treated with weekly cisplatin reached grade≥3 toxicity [18, 27] and 57% in three weekly group [14, 17, 24, 28]. …”
Section: Discussionmentioning
confidence: 99%